2022
DOI: 10.3390/buildings12101595
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors Analysis of Supply Chain Resilience of Prefabricated Buildings Based on PF-DEMATEL-ISM

Abstract: The supply chain for prefabricated buildings (PB) is vulnerable to the operation failure of node enterprises, with frequent damage occurring. Therefore, it is vital to establish an evaluation model of supply chain resilience (SCRE) to improve the ability to resist unanticipated risks. However, existing research falls short of explaining the hierarchy of the influential components. To fill this gap, this paper established an element-based system of PBSCRE affecting factors. The DEMATEL-ISM method, which combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…[20] To mitigate risk, the supply chain must be multidimensional and interdisciplinary, designed with the objectives of incorporating event preparedness, providing efficient and effective responses, and returning to or enhancing the original state after an interruption. In this paper, the resilience of prefabricated building supply chains (PBSCs) is defined as follows: under different types of risks, the prefabricated component supply system possesses the capability to resist, respond to, recover from, and adapt to interruptions in the supply chain [21]. Measurement metrics for the resilience of PBSCs are categorized into seven dimensions encompassing predictive capability, redundancy, robustness, and more, as detailed in Appendix A.…”
Section: Definitions Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] To mitigate risk, the supply chain must be multidimensional and interdisciplinary, designed with the objectives of incorporating event preparedness, providing efficient and effective responses, and returning to or enhancing the original state after an interruption. In this paper, the resilience of prefabricated building supply chains (PBSCs) is defined as follows: under different types of risks, the prefabricated component supply system possesses the capability to resist, respond to, recover from, and adapt to interruptions in the supply chain [21]. Measurement metrics for the resilience of PBSCs are categorized into seven dimensions encompassing predictive capability, redundancy, robustness, and more, as detailed in Appendix A.…”
Section: Definitions Referencesmentioning
confidence: 99%
“…This approach aims to achieve an in-depth analysis of the elements of various potential and measured variables and their interrelationships. Similar to the measurement of SCR, the measurement of resilience in PBSCs primarily focuses on predictive capability, redundancy, robustness, agility, adaptability, recovery capability, and learning ability [21,53,54]. This paper utilizes SEM to analyze the research, with the goal of verifying the alignment between the constructed model and research assumptions and analyzing critical risk factors in PBSCs.…”
Section: Pbsc Resilience Impact Factor Modelmentioning
confidence: 99%
“…Information response resilience includes information technology level, information response ability and information distribution accuracy [ 43 ]. The level of information technology covers the development of digital technologies such as the Internet of Things, big data, cloud computing, machine learning, blockchain and cyberphysical systems of the entire supply chain, through which information technology can not only enhance the visibility and transparency of the supply chain, but also monitor and warn risks in the supply chain in a timely manner [ 44 , 45 ]. Information responsiveness is the ability of enterprises in the supply chain to quickly adjust their production and operation activities based on external information [ 46 ].…”
Section: Supply Chain Resilience Evaluation Index Systemmentioning
confidence: 99%
“…the entire supply chain, through which information technology can not only enhance the visibility and transparency of the supply chain, but also monitor and warn risks in the supply chain in a timely manner [44,45]. Information responsiveness is the ability of enterprises in the supply chain to quickly adjust their production and operation activities based on external information [46].…”
Section: Plos Onementioning
confidence: 99%
“…In addition, Zhang et al found that the manufacturing of components and the assembly construction have a remarkable impact on prefabricated building supply chain resilience, whereas the transportation and storage of components had a lesser impact, and the information and partner factors had a strong moderating effect on the above processes [10]. Lu et al summarized 15 key impact factors of supply chain resilience for assembly building supply chain, and 6 highly concentrated factors were identified: risk management, inventory management, contingency planning, visibility, environmental risk, and information technology [31]. Wang et al explored 18 crucial factors on the resilience of the assembly building supply chain in terms of external and internal environments [13].…”
Section: Prefabricated Building Supply Chain Resiliencementioning
confidence: 99%